2011
DOI: 10.1007/s12206-011-0702-7
|View full text |Cite
|
Sign up to set email alerts
|

Determination of deposit thickness in natural gas cooler based on the measurements of gas cooling degree

Abstract: An original method for estimating fouled deposit thickness on the inside surfaces of natural gas cooler tubes is presented. This method does not require opening and inspecting a cooler as it is based on the measurement of gas cooling degree, i.e. the gas temperature difference between the cooler inlet and discharge. The deposit layer on the internal heat transfer surfaces is of semi-liquid consistency and its thermal conductivity coefficient has not been investigated until now. This paper describes the experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…The balance method is based on a comparison of the supplied and removed heat output using Equation (1). The method applicable to a crossflow cooler (Figure 2a) is described in detail in paper [1], while the results related to a double crossflow cooler (Figure 2b) are presented in this article.…”
Section: Balance Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The balance method is based on a comparison of the supplied and removed heat output using Equation (1). The method applicable to a crossflow cooler (Figure 2a) is described in detail in paper [1], while the results related to a double crossflow cooler (Figure 2b) are presented in this article.…”
Section: Balance Methodsmentioning
confidence: 99%
“…Figure 1 shows the real condition of a natural gas cooler fouled with impurities of an unknown composition. The authors of paper [1] identified the heat-transfer coefficient of the fouling layer in an experiment. Expressing a cooling capacity is also difficult due to the fact that the temperatures of the cooled medium and of the cooling medium change on the heat-transfer surface along the entire tube length [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…The principle thereof is based on the elementary relation applicable to the heat flux density q at unidirectional steady heat transfer in a planar board (layer) [4][5][6]…”
Section: Description Of the Methodology For Measuring The Thermal Conmentioning
confidence: 99%
“…The small neighbour's drops are collecting to the bigger drops until they are tearing down from the surface by the gravity or other forces. As drops are flow down the wall, they leaving clean surface where condensation can proceed [9].…”
Section: Condensationmentioning
confidence: 99%